Exploration of the medial border for laparoscopic D3 lymph node dissection in right hemi-colon cancer: a systematic review and meta-analysis - Wang, Minchen; Li, Zhiyuan; Fan, Xin; Chen, Jixiang; Han, He (Frontiers in Surgery, 2025)
IntroductionThe optimal medial boundary for lymph node dissection during laparoscopic radical right hemicolectomy for colorectal cancer remains uncertain. We investigated whether the superior mesenteric artery (SMA) or superior mesenteric vein (SMV) should serve as the medial border for D3 lymph node dissection in right hemicolon cancer.MethodsWe systematically searched the Cochrane Library, EMBASE, CNKI, VIP, Wanfang, ClinicalTrials.gov, and SinoMed databases through March 2024. Studies comparing SMA- and SMV-based medial borders were included according to predefined criteria. Outcomes analyzed included intraoperative parameters, postoperative recovery, lymph node yield, complications, and survival.ResultsCompared with the SMV group, the SMA group had more lymph nodes cleared (P = 0.001) and more positive nodes retrieved (P = 0.04), but also longer postoperative drain placement (P = 0.01). Intraoperative bleeding was higher in the SMV group (P = 0.01). Meta-analysis of patients’ postoperative overall survival (P = 0.927) and recurrence-free survival (P = 0.949) showed no significant differences in short-term prognosis between the two groups.DiscussionUsing the SMA's left border for laparoscopic D3 dissection is safe and feasible, providing higher lymph node yield without increasing major complications. However, this greater yield did not translate into improved short-term survival. The long-term prognostic effect of the SMA approach requires further investigation.Systematic Review Registrationidentifier (CRD42024502882).